The Cyber Kill Chain Methodology as a Business Defense Tool: A Systematic Review of Its Application and Efficacy - Dávila-Huayhuapuma, Junior E.; Vílchez-Roncal, Eduardo; Alvarado-Silva, Carlos A. (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study focuses on analyzing the detection and defense of cyber-attacks on companies, emphasizing the Cyber Kill Chain (CKC) model. Examining specialized articles reveals the widespread recognition and application of this structured methodology in cybersecurity. The model proves valuable for identifying and mitigating attack stages, facilitating early detection and a more effective response to security incidents. Results indicate its notable effectiveness in scrutinizing cyber attackers’ strategies throughout the attack process, with variations based on organizational size and industry. Adapting the model to specific contexts is crucial. Despite positive findings, limitations include restricted access to academic literature and potential biases in paper selection. The study recommends organizations integrate the CKC model into their cybersecurity strategies, advocating collaboration among experts, researchers, and professionals. This collaborative effort aims to address identified limitations, enhance understanding, and expand knowledge about the model’s effectiveness and adaptation to diverse environments. Overcoming these challenges will strengthen the application of the CKC model in combating cyber threats, ultimately providing enhanced protection for the information and systems of companies and entities in today’s digital landscape.